Assessing the Role of Screen Time and Digital Literacy in Student Learning at Learning Circle Inc., Olongapo City - Quintino, Bea Marie B.; Espiritu, Raymond D. (Future Science / FSH-PH Publications, 2025)
This research investigated the relationship between screen time and digital literacy of elementary students at Learning Circle, Inc., Olongapo City, Philippines after the excessive use of digital tools brought by COVID 19. A descriptive-correlational type of research design was used with 102 students who were surveyed through Likert-scale questionnaire. Students’ screen time exposure was of a moderate level, with the mean screen time exposure score 2.74 (SD = 0.80). In the aspect of digital literacy, students have an acceptable level with the overall mean 2.85(SD =0.73). Statistically significant differences were found between age and grade when analysed via ANOVA in screen time exposure and digital literacy. In particular, there was a segregation in the adoption of screen time exposure by age (F(8, 93) = 4.058, p < 0.001) and scholarship level (F(5, 96) = 4.683, p < 0.001). However, there was no significant sex difference observed (F(1, 100) = 0.122; p = 0.727). There were statistically significant, positive correlations between screen time exposure and e-literacy (r = 0.710, p-value < 0.001) showing in Pearson correlation analysis.). These results suggest that increased levels of screen time may stimulate the acculturation in digital literacy and call for equitable usage in educational settings. The results of the research have significant implications for educators and policy makers on how to effectively incorporate technology into the classroom as a means of promoting positive amounts of screen time.